2006
DOI: 10.1177/154405910608501011
|View full text |Cite
|
Sign up to set email alerts
|

ART and Conventional Root Restorations in Elders after 12 Months

Abstract: Successful use of atraumatic restorative treatment (ART) in children has been reported, but little information is available regarding its use in older adults. The hypothesis of this study was that survival rates of root restorations placed by both ART and the conventional technique were similar. Root-surface caries lesions in 103 institutionalized elders in Hong Kong were treated randomly by either: (1) the conventional approach-caries removed by dental burs, and the cavity filled with light-cured resin-modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
100
2
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(112 citation statements)
references
References 24 publications
4
100
2
6
Order By: Relevance
“…25,26,27 In the present study, the rate of success and survival was slightly lower than that reported previously (81% at the 6-month follow-up).…”
contrasting
confidence: 86%
See 3 more Smart Citations
“…25,26,27 In the present study, the rate of success and survival was slightly lower than that reported previously (81% at the 6-month follow-up).…”
contrasting
confidence: 86%
“…In contrast with these results, in 2006, Lo et al 25 conducted a study on a population similar to that used in our study and reported the lack of a significant difference in clinical performance when comparing both methods in 122 restorations (59 ART and 63 conventional restorations) using conventional and glass ionomer cement modified with composite resin. At the 12-month follow-up, nine ART restorations and six conventional restorations failed.…”
contrasting
confidence: 82%
See 2 more Smart Citations
“…[7] Old Glass-ionomer cements are biocompatible, achieving a chemical bond to enamel and dentin, and releases fluoride. These materials are aesthetically poor [27] Resinmodified glass-ionomers are indicated for high caries-risk patients. They are biocompatible, bond to enamel and dentin, possess thermal expansion and contraction characteristics that match tooth structure well, and have an anticariogenic effect and it also releases fluoride.…”
Section: Restorative Materialsmentioning
confidence: 99%